EVALUASI PERENCANAAN DAN KETERSEDIAAN OBAT PUBLIK UNTUK PELAYANAN KESEHATAN DASAR (PKD) DI DINAS KESEHATAN KABUPATEN REJANG LEBONG - , ARDIYANSAH SOFYAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Drug planning is one of the activities in medicine management performed and the responsibility of the Pharmaceutical and Medical Devices Division of Rejang Lebong Regencial Health Office. In general, there are many constraints in the planning and availability of drugs, such as haven't been formed Integrated Drug Planning Team, inaccurate drug plan, excessive drug stocks, stock out of drugs, dead stock of drugs, damaged and expired drugs. Given the importance of medicine management in order to achieve a quality health service, it is necessary that evaluation is need to do improve the planning and provision of drugs more effectively and efficiently. Objective: To evaluate the planning and availability of public medicines for basic healthcare that has been conducted by Rejang Lebong Regencial Health Office for the period 2010-2011. Method: This research is a descriptive type and used retrospective data. The data collected were both qualitative and quantitative. The former was collected through indepth interview, while the latter through observation of documents related to the planning and availability of public medicine for basic healthcare period 2010-2011. Results: By used assessment tools and indicators medicine management planning and the availability of drugs, the result showed that medicine management has not good. Human resources and facilities remain less capable and inadequate. In 2010 and 2011 the percentage of allocated medicine fund of the total medicine funding needed amounted to 83.07% and 70.49%